A study of correlation between iron deficiency anaemia and serum lipid profile in Indian adults in BRIMS, Bidar - Antappanavar, Vijaykumar B.; Biradar, Shivraj G.; Patil, Veerendra; Biradar, Prithviraj M.; Mithare, Shivkumar; Sharma, Ashish Kumar (International Journal of Advances in Medicine, 2017)
Background: Both iron deficiency anemia and dyslipidaemia are widely prevalent public health problems, especially in the Indian population. Some link has been suggested between the two potentially morbid conditions but a sufficient Indian study could not be found in this regard. Methods: This study was planned to find the changes in serum lipid profile in adult Indian patients with iron deficiency anemia and the effect of oral iron therapy on them. 100 iron deficiency anemia and 70 age and sex matched healthy controls, in the age group 18-35 years were investigated for any possible changes in serum lipid profile i.e., triglycerides, total cholesterol, high density lipoprotein cholesterol, very low density lipoprotein cholesterol. The patients were followed up after 3 months of oral iron therapy. Results: The results are shown as mean± standard deviation. Triglycerides and very low density lipoprotein cholesterol levels were found to be significantly (P <0.001) elevated in the iron deficiency anemia group (151.87 ± 48.06 mg/dl and 30.40 ± 9.71 mg/dl) as compared to controls (109.99 ± 30.81 mg/dl and 21.96 ± 6.69 mg/dl), whereas level of low density lipoprotein cholesterol were found to be significantly (P = 0.02) lower in patients (90.96 ± 41.55 mg/dl) as compared to controls (105.24 ± 26.45 mg/dl). However, after treatment (in 43 patients) there was significant (P <0.001) reduction in the levels of triglycerides and very low density lipoprotein cholesterol (111.56 ± 26.87 mg/dl and 22.30 ± 5.36 mg/dl) when compared to their pretreatment level (154.70 ± 53.89 mg/dl and 30.93 ± 10.84 mg/dl), whereas low density lipoprotein cholesterol levels did not show any significant change. Conclusion: These findings indicate that iron deficiency anemia in Indian adults is attended by abnormal serum lipid profile, which responds significantly to iron therapy.